Penyuluhan dan Pelatihan Peningkatan Pendapatan Petani Jamur Tiram dengan Menghasilkan Produk Olahan di Desa Dukuh Kecamatan Banyudono, Boyolali - Rahadhini, Marjam Desma; Lamidi (AJAD : Jurnal Pengabdian kepada Masyarakat, 2023)
Currently mushroom producers have sprung up everywhere, both oyster mushroom businesses, ear mushrooms, and so on. This is due to increased public awareness of the need for mushroom consumption, along with public understanding of the nutritional benefits it contains. This Community Service Program was carried out in Dukuh Gurung RT 11 / RW 03, Dukuh Village, with an oyster mushroom business partner, Mr. Surya Dahono Aji. The large amount of oyster mushroom production is not processed independently, the mushroom production is taken by vegetable traders. Business management still uses household business management. The purpose of this empowerment is to provide counseling and assistance on various processed oyster mushrooms. The implementation of activities by doing several stages, namely providing counseling to oyster mushroom business owners, stage 1 assistance, namely processed oyster mushroom products and stage 2 assistance, namely making simple financial reports. After this empowerment event, it is expected that there will be progress in understanding oyster mushroom processing